Digital leadership: shaping school effectiveness in the digital era - a meta-analysis - John Olayemi Okunlola (Educational Technology Quarterly)
This meta-analysis examines the relationship between digital leadership and school effectiveness in the digital era, synthesising evidence from 11 empirical studies across six countries. Against the backdrop of the Fourth Industrial Revolution, which has transformed educational paradigms through technologies like AI, IoT, and ICT, digital leadership has emerged as a critical factor in enhancing institutional outcomes. The study addresses five research questions, employing PRISMA-guided methodology to analyse peer-reviewed studies (2010--2024) from Scopus, Semantic Scholar, and Google Scholar. Using JASP 0.16.4 for random-effects modelling, the analysis revealed a robust pooled effect size (r = 0.672, p < 0.001), confirming digital leadership's significant positive impact on school effectiveness. Subgroup analyses showed notable variability, with Thailand (r = 0.784) and Malaysia (r = 0.553) demonstrating the strongest effects, while Indonesia (r = 0.123) and Bahrain (r = 0.209) exhibited weaker but still significant correlations. Publication bias assessments, including funnel plot asymmetry and trim-and-fill analysis, indicated minor bias but did not undermine the overall significance of findings. Fail-safe N tests (p = 0.000) further validated the results' robustness. The study highlights the need for context-specific digital leadership frameworks, particularly in regions with limited research representation. Practical implications include prioritising administrator training in data-driven decision-making and ICT integration, while policy recommendations emphasise infrastructure investment and standardised competency frameworks. Limitations include geographic underrepresentation and reliance on correlation-based studies. Future research should expand to underrepresented regions. This meta-analysis contributes to the growing evidence supporting digital leadership as a transformative force in 21st-century education.